Microstructure evolution in near isothermal forming of titanium alloy component. (2017) - Meng, M.; Fan, X.G.; Gao, P.F.; Guo, L.G.; Zhan, M.; Wei, K.
Abstract: A near isothermal forming technique was proposed to manufacture titanium alloy component, aiming to save the cost and obtain specific microstructure. In the near isothermal forming, the dies are heated to a temperature about 150℃ lower than that of workpiece. The relative low die temperature increases the die strength and decreases the hot corrosion of die. Meanwhile, the workpiece can be formed without significant die chilling and the tri-modal structure can be obtained by the coupling of deformation and phase transformation in non-isothermal forming. To obtain the objective microstructure, an analog experiment was carried out to investigate the effect of deformation parameters in the near-β phase field on microstructure morphology in the controlled cooling process. The evolution about phase volume fraction of primary and secondary alpha phase is obtained by quantitative metallographic analysis during cooling following hot deformation. The results show that the microstructure morphology can be changed by control the strain rate and thermal path. This will provide guidance for microstructure optimization in the near isothermal forging of titanium alloy large-scale integral components.